Kazakh Kuresi as an Intangible Cultural Heritage in the Context of Global Sports and International Recognition - Aisultan Zheldibay (Scientific Trends, 2024)
The article examines the Kazakh Sport as an element of intangible cultural heritage and, simultaneously, as a modern institutionalized sport. The dual logic of development is analyzed: "protection/inheritance" through UNESCO mechanisms and national registries, "sportization" through the standardization of rules, the bureaucratization of governance, media packaging, and international competitions. Based on the theoretical approaches of N. Elias and E. Dunning , as well as A. Guttman, it is shown that international recognition of sport The kures strengthens the cultural legitimacy of the practice, but simultaneously increases the risks of simplifying local meanings and "folklorizing" them to suit the expectations of the global sports market. Principles of a balanced development model are proposed: preserving the diversity of tradition within a unified competitive "core," prioritizing communities and practitioners in governance, and establishing ethical standards for representation and commercialization.
Keywords: Kuresi in Kazakhstan, UNESCO, intangible cultural heritage, sportization, institutionalization, globalization of sport, cultural policy, media.